Erratum - Team, Editorial (Southern African Humanities, 2019)
Erratum for Vol.29 (2016) for article: Porraz, G., Igreja, M., Schmidt, P. & Parkington, J.E. A shape to the microlithic Robberg from Elands Bay Cave (South Africa): 203–47.